1992
DOI: 10.1016/0014-5793(92)80937-c
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate binding specificity of the Tn‐antigen binding lectin from Vicia villosa seeds (VVLB4)

Abstract: -deoxy-D-galaetose (GalNDns) is a useful fluorescent probe to study the interaction of non-fluorescent sugars with tile B4 lectin from Vicia villosa seeds (VVLB4). Binding of the lectin to GalNDns leads to a L2-fold increase in Dansyl fluorescence with a concomitant 10 nm blue shift in its emission maximum. The strong binding of GalNDns (/4, --7.33 × 10 ~ M -~ at 20°C) is due to a favourable entropic contribution to the association process. Among the other sugars studied, GalNAc,rl.O.Ser followed by Mer, GalNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 20 publications
(10 reference statements)
5
26
0
Order By: Relevance
“…As demonstrated by previous workers and the present study, VVA bound not only to terminal a-linked GalNAc but also to terminal b-linked GalNAc [19]. In addition, VVA can bind to various kinds of GalNAc residues such as Cad antigen, Forssman antigen, GalNac a1 fi 3Gal [18,19,22]. More important, the present study demonstrated that VVA did bind to mannose residues of serotransferrin and that this binding was modulated by formalin fixation.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…As demonstrated by previous workers and the present study, VVA bound not only to terminal a-linked GalNAc but also to terminal b-linked GalNAc [19]. In addition, VVA can bind to various kinds of GalNAc residues such as Cad antigen, Forssman antigen, GalNac a1 fi 3Gal [18,19,22]. More important, the present study demonstrated that VVA did bind to mannose residues of serotransferrin and that this binding was modulated by formalin fixation.…”
Section: Discussionsupporting
confidence: 74%
“…This possibility is supported by the fact that VVA specifically recognizes Tn antigen (18)(19)(20)(21)(22)(23). A remaining question concerned the reason why the binding carbohydrate of VVA was not consistent with that of HB-Tn1, although both VVA and HB-Tn1 MAb bind specifically to Tn antigen.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, the binding (apparent K d ) of VVL-B4 to a-GalNAc derivatized BSA changed dramatically, by an order of magnitude, from >1,430 nM for 9 ligands per BSA to 129 nM for 13 ligands per BSA. These values and relative affinities are consistent with original studies establishing Tn-antigen (a-GalNAc-Ser) as a specific recognition epitope for VVL-B 4 (Puri et al, 1992).…”
Section: Importance Of Multivalent Interactionssupporting
confidence: 77%